Car innovations & autopilot: perception through the media in Kazakhstan (Herald of Journalism, 2019)
Due to the high cost of cars with autopilot in Kazakhstan (from 22 million tenge), personal reviews and comments on social networks about it are not common. Therefore, media texts remain the main source of information about self-driving cars. These texts are creating a defined communication environ- ment on the topic. To date, public perception formed under the media influence has a bias towards nega- tive. With the help of content analysis I have studied journalistic texts about car autopilots, published in domestic electronic media. According to the final results of the research: Kazakhstani mass media rarely publish materials on this particular topic; they can not maintain neutrality when covering the topic of autopilots (only 16%);domestic journalists more often resort to the use of words with negative labeling (55%); in a positive light the topic is gives only by business media; the audience under the media influ- ence and in the created communication environment gradually forms a negative attitude towards to the autopilot system.
Keywords: mass media, new technologies, cognitive perception, self-driving car, journalistic text.